Analysis of Financial Statement Fraud using the Fraud Hexagon in IDX Basic Materials Firms - Louisa Puspa Jelita; Yohanes Mario Pratama (IQTISHODUNA, 2026)
This study aims to analyze the effect of fraud hexagon theory on financial statement fraud among companies in the basic materials sector on the Indonesia Stock Exchange during the 2020-2023 period. Financial statement fraud is a type of occupational fraud that results in significant losses, underscoring the importance of identifying its underlying causes, particularly in capital-intensive industries such as the basic materials sector. Using a quantitative approach and logistic regression analysis on 308 firm-year observations, this study applies the Beneish M-Score to detect potential financial statement fraud. The independent variables represent six dimensions of the Fraud Hexagon: financial target (pressure), ineffective monitoring (opportunity), change in auditor (rationalization), no change in director (capability), political connection (arrogance), and related party transactions (collusion). The results of this study indicate that financial targets are positively associated with financial statement fraud. Meanwhile, ineffective monitoring, change in auditor, no change in director, political connection, and related party transactions have no effect on financial statement fraud. The study’s findings have practical implications, suggesting that financial pressure indicators should be closely monitored to strengthen corporate fraud prevention strategies.